3D-QSAR study and development of pharmacophore for serotonin 5-HT2A receptors agonists - Radan Milica; Nikolić Katarina; Vučićević Jelica; Oljačić Slavica; Agbaba Danica (Pharmaceutical Association of Serbia, Belgrade, Serbia, 2017)
All tested compounds show agonistic activity onserotonin5-HT2areceptors, which activation causes neuronal excitations, behavioral changes and platelet aggregation. The main aims of this study were to create 3D-QSAR(3D-Quantitative structure-activity relationship)model, analyse 3D-structure of the pharmacophore, validate the 3D-QSARmodel, and propose structural modification for novel 5-HT2aagonists.3D-QSAR modeling was applied to 51 agonists of 5-HT2areceptors. Dominant forms at physiologic pHof the examined compounds were optimized using the PM3 method and used for QSAR modeling. Data set was divided in two groups, training set of38 compounds, and test set of 13 compounds. Training set was used to build 3D-QSAR model, while test set was examined for the model validation. PLS (Partial Least Square Regression)method was used to develop 3D-QSAR model. Statistical parameters of the created and validated 3D-QSAR model,R2= 0.93, Q2=0.72, RMSEE=0.178, RMSEP=0.190 and R2 pred=0.63, indicate good prognostic capacity of the model.The3D-QSAR model was applied to analyse pharmacophore and to predict activity of other agonists of serotonin 5-HT2areceptors. Information obtained from the 3D-QSAR study indicated that presence of hydrogen bond donor and steric hot spot at a distance 14.80-15.20Å (v477:O-TIP), hydrophobic region and hydrogen bond donor at a distance of 2.40-2.86Å (v226:DRY-O), hydrogen bond donor and hydrogen bond acceptor at a distance of 1.60-2.00Å (v389:O-N1) and two hydrophobic regions at a distance 9.20-9.60Å (v23:DRY-DRY) are essential for agonistic activity on 5-HT2aserotonin receptors.